Minimization of the risk of a violation of continuity in development of IT-systems - Калмыков, Андрей Викторович (Eastern-European Journal of Enterprise Technologies, 2012)
The questions of violation of continuity in development of it-systems are considered. The principles of sustainable and balanced development of the IT-systems are formulated based on the decomposition on the logical and physical aspects